Communication barriers in the family - Koc-Kozłowiec, Barbara (Karkonoska Państwowa Szkoła Wyższa, 2012)
The art of communication - listening and speaking - is a major life skill, with a thorough influence on every human life. Remaining silent while the interlocutor speaks is not all that there is to the act of listening to messages. True listening is based on an intention to get involved in understanding of the other person, enjoying his or her presence, learning something from the conversation, giving assistance, or comforting the interlocutor.In the article the author describes obstacles (barriers), which render true listeningimpossible. These barriers have been identified by a group of young adults.
Keywords: speaking; listening; communication; family